The Influence of the Problem-Based Learning Model Assisted with Learning Videos on Learning Motivation, Critical Thinking Ability and Learning Outcomes - Fitriani, Nurul; Rosleny, Rosleny; Nawir, Muhammad (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2024)
Parallel with the progress of technology, the discourse on developing learning models has become a focus that attracts the attention of both practitioners and researchers. Explicitly, this requires an adaptive and accelerated attitude from education practitioners. This research aims to test the effect of the Problem-Based Learning model assisted by learning videos on learning motivation, critical thinking skills and student learning outcomes. Statistical accuracy is relied upon to ensure the quality of the results obtained as empirical evidence using a Quasi experimental approach and a non-equivalent control group design. Data was collected through observation, learning outcomes tests and questionnaires, as well as documentation from a total of 56 samples with details of 27 students from the Experiment class and 29 students from the Control class. Descriptive statistical and inferential analysis is used with other sets of analyzes to describe results by considering the ease of reading the research results. The findings ultimately show that there is an influence of the Problem-Based Learning model assisted by learning videos on both learning motivation, critical thinking skills and student learning outcomes with each significance 0.05.